2021
DOI: 10.3390/ijms22084108
|View full text |Cite
|
Sign up to set email alerts
|

The Mechanisms of the Development of Atherosclerosis in Prediabetes

Abstract: Lifestyle changes, such as overeating and underexercising, can increase the risk of prediabetes. Diabetes is one of the leading causes of atherosclerosis, and recently it became clear that the pathophysiology of atherosclerosis progresses even before the onset of diabetic symptoms. In addition to changes in platelets and leukocytes in the hyperglycemic state and damage to vascular endothelial cells, extracellular vesicles and microRNAs were found to be involved in the progression of prediabetes atherosclerosis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 117 publications
0
10
0
Order By: Relevance
“…At the same time, hyperglycemia up-regulates chronic inflammatory markers, increases the production of reactive oxygen species (ROS), leads to metabolic disorders and promotes the occurrence of prediabetesrelated complications. 38 On the one hand, dietary intervention limited energy intake and alleviated metabolic stress faced by cells. On the other hand, some nutrients from a healthy diet have special protective effects on cells.…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, hyperglycemia up-regulates chronic inflammatory markers, increases the production of reactive oxygen species (ROS), leads to metabolic disorders and promotes the occurrence of prediabetesrelated complications. 38 On the one hand, dietary intervention limited energy intake and alleviated metabolic stress faced by cells. On the other hand, some nutrients from a healthy diet have special protective effects on cells.…”
Section: Discussionmentioning
confidence: 99%
“…Hyperglycemia leads to increased hematopoiesis and ROS-producing neutrophils, as well as to the production of extracellular vesicles from vascular endothelial cells and leukocytes, which, in turn, facilitate atherosclerosis via ROS-producing NADPH oxidase and LDL-scavenging CD36. They also carry specific miRNAs that promote hematopoiesis and inflammation [47].…”
Section: Classical Risk Factors Hypercholesterolemiamentioning
confidence: 99%
“…As Figure 1A shows, CAR protein expression was detected by immunofluorescence analysis, and we observed that CAR was mainly localized in the cytoplasm compartment of endothelial cells (Figure 1A). We next studied the effect of CAR-selective agonist 6-(4-chlorophenyl) imidazo [2,1-b] [1,3]thiazole-5-carbaldehyde O- (3,4-dichlorobenzyl)oxime (CITCO) on endothelial cell viability. For this purpose, HUVEC monolayers were pretreated with CITCO (0.1-3 µM) or vehicle (0.1% DMSO) for 24 h. As illustrated in Figure 1B, no effects on endothelial cell viability were detected at the different CITCO concentrations used.…”
Section: Car Is Expressed In Human Endothelial Cellsmentioning
confidence: 99%
“…Atherosclerosis involves an inflammatory response, consisting of intimal accumulation of leukocytes and lipid-laden macrophages throughout the entire atherogenic process [1,2]. Endothelial dysfunction, one of the earliest stages of atherogenesis, leads to a prothrombotic and proinflammatory phenotype of the endothelium which induces leukocyte attachment and subsequent migration [3].…”
Section: Introductionmentioning
confidence: 99%